Brand-Driven Economic Behavior: Analyzing the Impact of Brand Consciousness and Perceived Value on Luxury Beauty Purchases at Sephora - Hasanah, Uswatun; Setyaning, Alldila (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study investigates the influence of terminal values, instrumental values, and brand consciousness on the behavioral intentions of Generation Z consumers in Indonesia toward purchasing luxury beauty products at Sephora. The research is grounded in Self-Completion Theory and adapts a conceptual framework from Kautish et al. (2020). Using a quantitative approach with data collected from 296 respondents, this study employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the hypotheses. The findings indicate that both terminal and instrumental values significantly affect brand consciousness. Moreover, brand consciousness strongly influences behavioral intention and also mediates the relationship between values and purchase intentions. The results emphasize that Gen Z’s consumption behavior in the luxury beauty sector is not only driven by product functionality and prestige, but also by deeper psychological needs such as self-expression and value alignment. These insights offer strategic implications for marketers aiming to create emotionally resonant and value-driven brand experiences in emerging markets like Indonesia